(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Software-Defined Networking (SDN) offers a flexible and dynamic network architecture that is increasingly adopted for modern network management. However, the inherent centralization of the control plane makes SDNs vulnerable to Distributed Denial of Service (DDoS) attacks, which can disrupt network performance and availability. This paper presents a quantitative analysis of security enhancements in SDN environments to mitigate DDoS attacks. The research investigates various security mechanisms, including flow monitoring, rate limiting, and machine learning-based anomaly detection, by simulating DDoS attack scenarios in an SDN testbed. Key performance metrics, such as network throughput, latency, packet loss, and attack detection accuracy, are evaluated to assess the effectiveness of each security enhancement. Results indicate that while all security mechanisms improve resilience against DDoS attacks, machine learning-based solutions offer the best trade-off between detection accuracy and minimal performance degradation. The findings provide valuable insights for the development of robust security frameworks in SDN environments, ensuring reliable and efficient operation in the face of malicious traffic. Recommendations for future research include exploring hybrid security mechanisms and scaling solutions for large-scale networks.